Spectral Characteristics of Resonant-Link Inverters - Finney,SJ; Green,TC; Williams,BW (IEEE Transactions on Power Electronics, 1993)
Improvement in the frequency spectrum of resonant-link inverters does not match the increase in switching frequency because of the restriction of integral pulse modulation schemes such as delta modulation. Comparisons of low-frequency pulse width modulation with high-frequency delta modulation show that the spread spectrum of delta modulation may cause problems owing to low-frequency harmonics, despite a better total harmonic distortion. An assessment of total losses, for a bipolar junction transistor Darlington example, is used to set the operating frequency in each modulation case. © 1993 IEEE